THINK TALK WRITE STRATEGY ON STUDENTS’ WRITING ABILITY - EFFRINA YURICKI (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2024)
: Speaking skills are skills that enable us to communicate effectively. This skill has the most important goal for student success, especially for class XI of SMA because they will face the era of globalization in the world. As for the problems faced by class XI students of SMA Darus Su'ada Al-Ahad, most of them are not able to speak English. In this study, researchers applied the HOTS method in debate to improve students' speaking skills, especially in class XI of the SMA. By using the HOTS method and debate which is a learning concept where students are given the opportunity to start speaking through the provision of stimulus material so that students think critically, creatively, collaboratively, and communicatively, then students are able to present the ideas that are in their minds. This research is said to be successful; it can be seen from the results of the comparison of pre-test and post-test scores. Here, the researcher collects data through a mixed-method in which the researcher obtains data from the results of observations first and then from the results of the comparison of pre-test and post-test scores. As for the benefits of this research, firstly for a teacher using this method will not make students feel bored in following the learning process. Second, for other researchers, the results of this study can be used as a reference if they want to do similar research.